DYNAMICS OF PHYSICAL DEVELOPMENT OF STUDENTS WITH ONE AND TWO TIME COMPULSORY LESSONS (World Economics and Finance Bulletin, 2021)
Sports and physical culture improve health and thereby increase performance. All studies haveproven the positive effect of regular exercise on work activity. A lot of talk and discussion about the need for regular physical education of students in fact remaingood intentions. Deans' offices, drawing up the schedule of compulsory physical education classes,are forced to reduce the number of hours of physical education. This is due to the fact that physicaleducation is classified as a humanitarian discipline. This work examines the dynamics of the development of physical qualities with one and twophysical education lessons